Muddy street scene, Skagway, Alaska, October 1897. - Hegg, Eric A., 1867-1948 (1897)
Shows Clancy's Saloon to the right. Caption on image: "The Main Business Street Skaguay Alaska, Oct. 1897" Original image in Hegg Album 7, page 16.